The news from Ireland : foreign correspondents and the Irish revolution - Walsh, Maurice (I.B. Tauris, 2011)
The Anglo-Irish war of 1919-1921 was an international historical landmark: the first successful revolution against British rule and the beginning of the end of the Empire. However, the Irish revolutionaries did not win their struggle on the battlefield - their key victory was in mobilising public opinion in Britain and the rest of the world. Journalists and writers flocked to Ireland, where the increasingly brutal conflict was seen as the crucible for settling some of the key issues of the new world order emerging from the ruins of World War I. The News from Ireland vividly explores the work o.